Impact of a pediatric nursing emergency preparedness program for COVID on Nurses’ knowledge, skills and confidence - Venkatesan, Latha; Joshi, Poonam; Susaimuthu, Cecilia M.; Murry, Lumchio L.; Simak, Kiran S.; Sucheta,; Dabas, Suman (International Journal Of Community Medicine And Public Health, 2023)
Background: Coronavirus disease-2019 (COVID-19) mainly affects adults and the proportion of children with COVID 19 illness has remained low although it is showing an increasing trend with each wave of the pandemic. This article reports the impact of a pediatric nursing emergency preparedness program on COVID-19 (PNEPPCO) on the knowledge and confidence of nurses in a tertiary hospital. Methods: A selected number of common pediatric nursing skills that could be likely to be useful for care of children with COVID 19 illness were earmarked for the content of the training program. The training methodology consisted of a self-learning phase for 5 days, skill demonstration and practice for one day, and a preceptorship phase in the pediatric clinical area for 2 days. A total of 300 nurses were trained. Results: The mean age of the participants was 32.1±6.5 years. A majority (68.1%) of them was female and had a bachelor’s degree in nursing (68.1%). Most of them (85.1%) didn’t have prior experience of working in pediatric areas. There was a significant improvement in the level of knowledge (12.57±2.96 vs. 16.36±4.26, p=0.001) and confidence (p=0.001) in performing pediatric skills among the participants after the training program. Conclusions: The use of a multifaceted training methodology led to improvement in knowledge and skills in managing sick children among nurses. Building the nurses’ capacity to face new challenges in the near future will boost their morale and ensure that the quality of patient care stays uncompromised even during crisis situations.